Distributed Learning Ecosystems Concepts, Resources, and Repositories - Otto, Daniel; Scharnberg, Gianna; Kerres, Michael; Zawacki-Richter, Olaf.; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer VS, 2023)
This open-access book is based on the observation that learning ecosystems are increasingly established in higher education institutions. However, an important aspect that is still missing is their interconnectedness. Consequently, the book intends to close this gap by introducing the concept of a distributed learning ecosystem (DLE). A DLE follows the idea of establishing an interlinkage between decentralised learning ecosystems (consisting of content repositories and educational resources) and thus serves as an integrated approach that enables learners to access and use learning content and share resources. About the Editors Dr. Daniel Otto is currently interim professor for the chair of digital education in schools at the University of Oldenburg. His research focuses on educational technology, particularly Open Educational Resources (OER) in higher education. Dr. Gianna Scharnberg holds a PhD from the University of Duisburg-Essen and has conducted several research projects in adult education. She currently works as a consultant for E-Learning and Knowledge Transfer for the German Foundation for Commitment and Volunteering. Prof. Dr. Michael Kerres is professor of educational science at the University Duisburg-Essen. He holds the chair of educational media and knowledge management and is director of the University's Learning Lab. Prof. Dr. Olaf Zawacki-Richter has been involved in the design and development of digital study programs for over 20 years. He is professor of educational technology at the University of Oldenburg and director of the Center for Open Education Research (COER) at the Institute of Education.
Distributed Learning Ecosystems -- Distributed learning ecosystems in education -- The shift toward openness in education and the implications for learning ecosystems and ecologies -- The role of institutional repositories in higher education -- The Typologies of (Open) Online Courses and their Dimensions, Characteristics and Relationships with Distributed Learning Ecosystems, Open Educational Resources, and Massive Open Online Courses -- Open textbooks in higher education teaching -- Reuse of OER, a process model approach -- Quality of OER -- Development of an Austrian OER certification for higher education institutions and their employees -- Creating More Generous and Sustainable Educational Futures with OER -- Reflecting Open Practices on Digital Infrastructures -- The Technical Specifications and Requirements for Connecting OER Repositories Using the LOM Standard -- Version management in a distributed infrastructure for Open Educational Resources -- Developing a metadata profile for higher education OER repositories -- A Trusted Learning Analytics Dashboard for displaying OER.
Keywords: Education, Higher; Adult education; Technical education; Teaching; Teachers -- Training of; Higher Education; Adult Education; Technology and Design education; Pedagogy; Teaching and Teacher Education